Pediatric Medical Resuscitation: A Simulation Curriculum - Corey Heitz (Association of American Medical Colleges, 2010)
Abstract This resource is a curriculum designed to give residents experience in managing a seriously ill infant/child as well as to increase their ability to lead a resuscitation team. This curriculum is intended to be used during the introductory month to emergency medicine, but it can be performed at any time during training. The curriculum contains five scenarios covering bradycardia with a high-degree block, supraventricular tachycardia, septic shock, respiratory distress with respiratory failure, and cardiac arrest. Each resident is the team leader for one case; there is a discussion-style debriefing after each case, with key informational points highlighted. Each case has a specific critical actions checklist that is filled out for the resident running that particular case. This curriculum has been designed to assist in resident training in pediatric resuscitation. Emergency physicians, as well as pediatricians, must be knowledgeable and comfortable in the event of a pediatric emergency, including arrests and critically ill patients. However, the event rate of these in practice is low. Without practice, the skills and knowledge necessary to adequately care for these patients may not be maintained. In addition, without exposure to the events, anticipation and stress levels are high when one does occur. Initial measures of the curriculum effectiveness, via the responses to a survey of residents who participated, show that they found it highly valuable. All responses to the questions "Did this improve your comfort level?" and "Did this improve your level of knowledge?" were 4 or 5 on a 5-point Likert scale.